Peak exposures to main components of ash and gaseous diesel exhausts in closed and open ash loading stations at biomass-fuelled power plants. (October 2017) - Laitinen, Juha; Koponen, Hanna; Sippula, Olli; Korpijärvi, Kirsi; Jumpponen, Mika; Laitinen, Sirpa; Aatamila, Marjaleena; Tissari, Jarkko; Karhunen, Tommi; Ojanen, Kari; Jokiniemi, Jorma; Korpinen, Leena
Abstract: Fly and bottom ashes are collected at power plants to reduce the environmental effects of energy production. However, handling the ashes causes health problems for operators, maintenance workers and truck drivers at the power plants. Hence, we evaluated ash loaders' peak inhalation exposures to the chemical components of ash and diesel exhausts in open and closed ash loading stations at biomass-fuelled combined heat and power plants. We also carried out chemical and morphological analyses of the ashes to evaluate their health hazard potential in order to find practical technical measures to reduce workers' exposure. On the basis of X-ray diffraction analyses, the main respirable crystalline ash compounds were SiO2, CaSO4, CaO, Ca2 Al2 SiO7, NaCl and Ca3 Al2 O6 in the fly ashes and SiO2, KAlSi3 O8, NaAlSi3 O8 and Ca2 Al2 SiO7 in the bottom ashes. The short-term exposure levels of respirable crystalline silica, inhalable inorganic dust, Cr, Mn, Ni and nitric oxide exceeded their Finnish eight hours occupational exposure limit values in the closed ash loading station. According to our observations, more attention should be paid to the ash-moistening process, the use of tank trucks instead of open cassette flatbed trucks, and the sealing of the loading line from the silo to the truck which would prevent spreading the ash into the air. The idling time of diesel trucks should also be limited, and ash loading stations should be equipped with exhaust gas ventilators. If working conditions make it impossible to keep to the OEL values, workers must use respirators and protect their eyes and skin. Highlights: Health risks caused by crystalline silica compounds were found in FA and BA. Air concentrations of dust, SiO2, Cr, Mn, Ni and nitric NO were high during loading. Synergistic health effects on upper and lower respiratory system are possible. Technical measures and PPEs are essential for the safe loading of ash.